The Effectiveness of the Addition of Platelet-Rich Fibrin to Bovine Xenografts in Sinus and Bone Ridge Augmentation: A Systematic Review - Katia Idiri; Octave Bandiaky; Assem Soueidan; Christian Verner; Emmanuelle Renard; Xavier Struillou (Journal of Functional Biomaterials, 2023)
Dental implants sometimes need bone augmentation to recreate an adequate bone height and volume. Numerous bone augmentation techniques have been described, and, currently, the most commonly used bone graft procedure is xenografts with deproteinized bovine bone mineral (DBBM). The addition of platelet-rich fibrin (PRF) to DBBM has already shown better performance than DBBM alone in restoring intrabony periodontal defects, but the role of PRF in preimplantation bone grafts is still not clear. The objective of this systematic review was to evaluate the efficacy of the adjunction of PRF or L-PRF to DBBM in bone ridge augmentation procedures. Clinical randomized controlled studies using PRF associated with DBBM were included. In April 2023, three electronic databases (PubMed, Cochrane, and Web of Science) were searched. The search strategy was performed according to PRISMA guidelines. The risk of bias assessments were performed using the Cochrane Collaboration tool. A total of seven articles were included and analyzed. The results show no statistically significant effect of PRF added to DBBM compared to DBBM alone in the sinus lift procedure but do show an effect in the reduction in bone graft resorption in one study of mandibular guided bone regeneration.